SUBSTORMS DURING THE IMS PERIOD OBSERVED BY SOUNDING ROCKETS - ナガタ, タケシ; ヒラサワ, タケオ; フクニシ, ヒロシ; ヤマギシ, ヒサオ; キムラ, イワネ; オガワ, トシオ; NAGATA, Takesi; HIRASAWA, Takeo; FUKUNISHI, Hiroshi; YAMAGISHI, Hisao; KIMURA, Iwane; OGAWA, Toshio (1980)
P(論文) Experimental results obtained by the sounding rockets at Syowa Station, Antarctica, are briefly summarized. The electron density profiles in auroras were measured by the rockets which penetrated into intensely bright (∿30kR for OI 5577 Å), bright (∿10kR) and weak (∿5kR) auroras. The E-region electron density amounts to ∿1.2×(10)^6 el/(cm)^3,∿5.0×(10)^5 el/(cm)^3 and ∿6.0×(10)^4el/(cm)^3 for intensely bright, bright and weak auroras respectively, while it is ∿6.0×(10)^3el/(cm)^3 for no aurora during the night. The electron density in the D-region beneath the lower boundary of an intensely bright arc (75-98 m in altitude) is also considerably enhanced, up to 0.7-1.0×(10)^6 el/(cm)^3. In bright auroral arcs, the electric field becomes small and points in the equatorward direction, whereas it becomes large with the predominant westward direction in the near space outside of a bright auroral arc. The electric field fluctuations (up to 240Hz in frequency) are greatly enhanced in auroras over a wide frequency range, at altitudes of 100-120km. Various kinds of VLF and HF emissions are observed in the auroral ionosphere. Characteristics of these emissions and their relations to the precipitating electron flux are discussed. departmental bulletin paper